2013
DOI: 10.1074/jbc.m113.514877
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 90-α Mediates Aldo-Keto Reductase 1B10 (AKR1B10) Protein Secretion through Secretory Lysosomes

Abstract: Background: Aldo-keto reductase 1B10 (AKR1B10) protein is a new tumor biomarker in humans. Results: Heat shock protein 90␣ (HSP90␣) is a chaperone molecule that mediates transportation to lysosomes and secretion of AKR1B10. Helix 10 of AKR1B10 protein mediates its interaction with HSP90␣. Conclusion: HSP90␣ mediates AKR1B10 secretion through binding to its helix 10 domain. Significance: This finding is significant in exploiting the use of AKR1B10 in cancer clinics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 37 publications
(22 reference statements)
1
24
0
Order By: Relevance
“…AKR1B10 was first identified in HCC and then characterized as a secretory protein . In the past years, clinical histological studies of HCC have identified AKR1B10 as a marker for prognosis and risk stratification of HCC .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AKR1B10 was first identified in HCC and then characterized as a secretory protein . In the past years, clinical histological studies of HCC have identified AKR1B10 as a marker for prognosis and risk stratification of HCC .…”
Section: Discussionmentioning
confidence: 99%
“…AKR1B10 is a secretory protein up‐regulated in HCC . AKR1B10 can eliminate cytotoxic and carcinogenic α and β‐unsaturated carbonyl compounds and regulate de novo fatty acid/lipid synthesis .…”
mentioning
confidence: 99%
“…In agreement with our studies, HSP90α has been described in the cytoplasm of 3T3 cells (56, 57) and increased expression of HSP90 (58), and in particular, the isoform HSP90α (59) has been observed in cancer compared to that in normal tissue. Furthermore, recent studies have shown that HSP90 (60), including HSP90α, regulates the migration and invasion of cancer cells (57, 61) and can transport client proteins to lysosomes for secretion (62). Moreover, a variant of HSP90α has been shown to chaperone some proteins to exosomes in a variety of cancer cell lines (61).…”
Section: Discussionmentioning
confidence: 99%
“…Hsp70 and Hsp40 also bind HSF1, but do not inhibit its transcriptional activity. Under stress, Hsp90 releases HSF1, which forms trimers, relocates to the nucleus, and induces the expression of HSPs (Morimoto 2008;Luo 2010Luo , 2013. Hsp90 inhibitors have been developed to reverse the permissive role of Hsp90 in tumorigenesis.…”
Section: Hsp90mentioning
confidence: 99%